SHAPING A CULTURE OF CLEAN AND HEALTHY LIVING BEHAVIOR AT SMP NEGRI 4 LHOK SUKON THROUGH EDUCATION AND PROMOTION PROGRAMS - Lensoni, Lensoni; Sakinah, Juliana (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
Clean and Healthy Living Behavior (CHLB) is a critical component in enhancing public health, particularly within school environments. This study investigates the development of a CHLB culture at SMP Negeri 4 Lhok Sukon through structured education and promotion initiatives. Employing a quantitative descriptive survey approach, data were collected via questionnaires, observations, and document analysis. The findings reveal significant improvements in students' knowledge, attitudes, and practices regarding CHLB following the implementation of educational and promotional programs. Key factors contributing to the program's success included the active participation of teachers, parents, and school administrators, fostering a supportive environment for behavioral change. The study underscores the effectiveness of direct counseling and interactive education over traditional promotional media in cultivating sustainable healthy living habits. Recommendations include enhancing sanitation facilities, integrating CHLB into the curriculum, and organizing regular health workshops to further reinforce these behaviors.